(untitled) (American Journal of Technology and Applied Sciences, 2025)
In this study, the chemical composition and antibacterial activity of essential oil extracted from Rosa canina were investigated using gas chromatography–mass spectrometry (GC-MS). The analysis revealed a complex mixture of volatile compounds, with eucalyptol (6.51%) and α-terpineol (0.61%) identified as the major components. Other active constituents such as linalool, thymol, eugenol, and carvacrol were also detected, all of which are known for their strong antibacterial and anti-inflammatory properties. Antibacterial activity, assessed via the disk diffusion method, showed the highest inhibition zone against Staphylococcus aureus (20–28 mm). The minimum inhibitory concentration (MIC) test demonstrated that bacterial growth was completely inhibited at concentrations ranging from 0.125% to 0.5%. Correlation analysis revealed a strong positive relationship between phenolic compound content and antibacterial activity (r > 0.85, p < 0.05). The results confirm the potential of Rosa canina essential oil as a natural antibacterial agent suitable for use in the pharmaceutical, cosmetic, and food industries.